Both Physical and Virtual: On Immediacy in Esports - David Ekdahl; David Ekdahl (Frontiers Media S.A., 2022)
This article strives to make novel headway in the debate concerning esports' relationship to sports by focusing on the relationship between esports and physicality. More precisely, the aim of this article is to critically assess the claim that esports fails to be sports because it is never properly "direct" or "immediate" compared to physical sports. To do so, I focus on the account of physicality presented by Jason Holt, who provides a theoretical framework meant to justify the claim that esports is never properly immediate and therefore never sports. I begin by motivating Holt's account of physicality by contrasting it with a more classical way of discussing physicality and sports, namely in terms of physical motor skills. Afterwards, I introduce Holt's account of physicality as immediacy and engage with its assumptions more thoroughly to problematize the claim that esports is fundamentally indirect. Lastly, I argue that the assumption that esports necessarily lacks immediacy is based on a narrow understanding of body and, consequently, of space. In response, I offer a different way of thinking about body and space, focusing on the subjective, bodily engagement of the esports practitioners with their practice, whereby physical space and virtual space can be appreciated as immediately interconnected during performance in a hybrid manner. In providing such an account, the article contributes directly to the broader, growing discussion on the relationship between physicality and virtuality in an increasingly digital world.